Judging severity of unethical workplace behavior: Attractiveness and gender as status characteristics - Galit Klein; Ze'ev Shtudiner (BRQ Business Research Quarterly, 2021)
This research focuses on the role of gender and physical attractiveness in judging severity of unethical workplace behavior. Scenarios with possible ethical dilemmas (commonly referred to as "gray areas" of behavior) were displayed to 4,483 subjects. Our findings show that "gray area" behavior was evaluated as more ethical if performed by male employees compared with women. We also found that attractiveness moderated the connection between gender and tolerance toward unethical work behavior. People judge more severely the same unethical action by plain-looking employees rather than attractive-looking employees, in accordance with the attractiveness-leniency effect-but only for women perpetrators. The physical attributes of men were not found to be relevant. We explore a number of explanations for this discrimination based on Expectation States Theory and Social Role Theory.
Keywords: C91; J71; 650; Ethical judgment; gender; evaluation biases; physical attraction (PA); unethical work behavior